Pogranicze fotografii – znaczenie stopklatki w dziele filmowym - Sosnowska, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Freeze frame is a still picture in the course of a movie or television film, made by running a series of identical frames or by stopping a reel or videotape at one desired frame. It is a peculiar element of the word in the cinematography. He is standing on the border of old form of photographic stopping the image and in the painting frame of the works of art and is a resultant of filmed, movable reality. Establishing the definition freeze frame is a purpose of the article and of portraying ways for it of using in the cinematography.